If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Oblicz to!
6-3*x = 0
y = 0.5*x^2-3*x+4.5;0.5;-3;4.5
-(((-3)^2-(0.5*4*4.5))/(0.5*4))
-(-3/(0.5*2))
0.5*0^2-(0*3)+4.5
| (1/8).(2x/5)= | | 0.6b+3.7=0.4b+11.7 | | 2y-17=6y-5 | | 36=n^2+5n | | v=x-yz | | 3*-y=0 | | lnx=3.3 | | 3*-y=4 | | 1/2ln(4x^2-7x)^7/6 | | 0.12x(-12)= | | 6.9x-3.2=3.7 | | 4z+5=z-2 | | Radical625/10 | | 10x^2+6x-23=0 | | {625/19} | | 2(-4)+3y=5(-4)-y | | 0=2t(-3t+20) | | 4/5/3/4= | | 12x-29=8(3-x)-283 | | 3+2.7x=9.5+3.2x | | ln(5x(x+3))=4 | | 11x+5=9+21 | | -5x-3=-27 | | 6z+3=17-z | | o(n)=2(5)-1 | | -13+x=32 | | 4y+9y+8y+5= | | 17y-13+6y^2-14y+5= | | 5(x^2)+15x=e^4 | | C=30+0.7Y | | 28(2x-1)=7(x+3)2x | | 2+4(x-1)=5-8(x-7) |